Biopersistent granular dust and chronic obstructive pulmonary disease: a systematic review and meta-analysis. - Irene Brüske; Elisabeth Thiering; Joachim Heinrich; Katharina Huster; Dennis Nowak (PLoS ONE)
Objective Applying a systematic review to identify studies eligible for meta-analysis of the association between occupational exposure to inorganic dust and the development of chronic obstructive pulmonary disease (COPD), and conducting a meta-analysis. Data sources Searches of PubMed and Embase for the time period 1970-2010 yielded 257 cross-sectional and longitudinal studies on people exposed to inorganic dust at the workplace with data on lung function. These studies were independently abstracted and evaluated by two authors; any disagreement was resolved by a third reviewer. Of 55 publications accepted for meta-analysis, 27 investigated the effects of occupational exposure to biopersistent granular dust (bg-dust). Methods A random effects meta-analysis allowed us to provide an estimate of the average exposure effect on spirometric parameters presented in forest plots. Between-study heterogeneity was assessed by using I(2) statistics, with I(2)>25% indicating significant heterogeneity. Publication bias was investigated by visual inspection of funnel plots. The influence of individual studies was assessed by dropping the respective study before pooling study-specific estimates. Results The mean FEV1 of workers exposed to bg-dust was 160 ml lower or 5.7% less than predicted compared to workers with no/low exposure. The risk of an obstructive airway disease--defined as FEV1/FVC < 70%--increased by 7% per 1 mg · m(-3) respirable bg-dust. Conclusion Occupational inhalative exposure to bg-dust was associated with a statistically significant decreased FEV1 and FEV1/FVC revealing airway obstruction consistent with COPD.